Carbamazepine-Induced Toxic Epidermal Necrolysis Managed by Mobile Teledermatology in COVID-19 Pandemic in Rural Nepal - Vikash Paudel; Deepa Chudal (Case Reports in Dermatological Medicine)
Toxic epidermal necrolysis is a life-threatening dermatological emergency with high mortality if not treated in time. Here we report a case of toxic epidermal necrolysis due to carbamazepine in rural Nepal in COVID-19 pandemic who was successfully treated with the help of mobile teledermatology. The clinical impression of toxic epidermal necrolysis was made from “WhatsApp” video calls using a smart phone. The supportive features were the history of starting of carbamazepine 2 weeks prior for seizure disorder, clinical findings in serial photographs of skin with 40 percent body surface area involvement of necrotic skin lesions and bulla, and involvement of oral mucosa and eyes. The patient was immediately asked to stop carbamazepine and was treated with intravenous fluids and systemic steroids along with symptomatic management. As the whole world was suffering from lockdown due to COVID-19 crisis, it was impossible for the rural area patient to visit a dermatologist. Thus, with the help of paramedics staff in a community health center and mobile teledermatology, the patient was diagnosed as carbamazepine-induced toxic epidermal necrolysis and treated successfully with good outcome.